Analisis Peran Account Officer dalam Penyelesaian Pembiayaan Murabahah Bermasalah di Era Pandemi Covid-19 (Studi Kasus KSPPS Karisma Cabang Magelang) - Shinta Wahyu Ningrum; Hadi Sasana; Ayunda Putri Nilasari (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
This research was conducted by highlighting the problems regarding the role of the account officers in solving problematic Murabahah financing in the era of the Covid-19 pandemic at KSPPS Karisma Magelang Branch. The research method used is qualitative with a descriptive approach so as to produce descriptive data in the form of written or spoken words, words, pictures, and numbers book. The sources of data obtained are primary data and secondary data. The data analysis technique used is the interview method, the observation method, and the documentation method. The results of this study indicate that from research conducted by the author at KSPPS Karisma Magelang Branch about the role of the account officer used in the settlement of problematic Murabahah financing are the factors that affect the quality financing such as such as member character, member financial analysis, capital structure, production capability, business cycle, guarantee, monitoring, and coaching.